2015
DOI: 10.1021/acs.inorgchem.5b02493
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Activation of Oxidized Sulfur Ligands and Implications for the Biological Activity of Ruthenium(II) Arene Anticancer Complexes

Abstract: Surprisingly, the anticancer activity of half-sandwich Ru arene complexes [(η(6)-arene)Ru(en)Cl](+) appears to be promoted and not inhibited by binding to the intracellular thiol glutathione. Labilization of the Ru-S bond allowing DNA binding appeared to be initiated by oxygenation of the thiolate ligand, although oxidation by itself did not seem to weaken the Ru-S bond. In this study, we have investigated the solvation and acidic perturbations of mono (sulfenato) and bis (sulfinato) oxidized species of [(η(6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…Therefore, its properties as antioxidant, and its role in cancer prevention require the understanding of the complex activity‐toxicity relationship. [1a], [5a], Additionally, whilee compound 5 resulted not selective the complex 4 showed to be 3–8 times less active against a non‐tumor cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, its properties as antioxidant, and its role in cancer prevention require the understanding of the complex activity‐toxicity relationship. [1a], [5a], Additionally, whilee compound 5 resulted not selective the complex 4 showed to be 3–8 times less active against a non‐tumor cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolysis and the loss of one or more ligands are important processes in the mechanism of action of these water soluble ruthenium drugs due to increasing the number of potential targetable molecules. [1d], We have been interested in this field for years, firstly synthesizing and studying the family of water‐soluble ruthenium complexes [RuCpX(L 1 )(L 2 )] n + (X = Cl; L 1 , L 2 = PPh 3 , PTA, mPTA, mTPPMS) . Later on we studied also the effect on the antiproliferative activity of the bis‐ N ‐methylated PTA N , N′ ‐dimethyl‐1,3,5‐triaza‐7‐phosphaadamantane (dmPTA) and its derivative 3,7‐H‐3,7‐dimethyl‐1,3,7‐triaza‐5‐phosphabicyclo[3.3.1]nonane (HdmoPTA) .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidized thiolate ligands are found in several metalloproteins which actually require the oxidized thiolate ligand for their activity: Nitrile hydratase is a well-studied example (10,11). Thiolate oxidation may also lead to labilization of the oxidized ligand so that it can readily be substituted; this effect is believed to be important for Ru anticancer predrugs where the oxidized thiolate of the predrug is replaced by a nucleotide base (12)(13)(14)(15).…”
Section: Photooxidation Of Organic Sulfides and Metal Thiolatesmentioning
confidence: 99%
“…Since Ru(II) arene complexes exhibit a higher anticancer activity and lower toxicity than traditional platinum drugs, they are considered as promising lead Ru(II)-based anticancer drugs of the near future. 1,2 Some researchers have revealed that the anticancer activities of Ru(II) arene complexes are affected largely by the property of their chelating ligands to various extents. Beckford and coworkers exhibited the good anticancer activity of Ru(II) arene complexes with thiosemicarbazones against different human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%